Влијанието на еврото врз надворешнотрговската размена на Европската Унија - Макревска, Елена (Економски факултет, УКИМ, Скопје, 2013)
The European Union`s trade accounts for about one-fifth of the total trade of goods and services in the world, making it the largest trade player. Such position is a result of the existence of the Common market and the Common Trade Policy, which gives the Union exclusive right and power to represent the interests of member countries in the multilateral trading system and to negotiate as a single entity. The scope of the foreign policy is further expanded by the Treaty of Lisbon, which includes trade in services, foreign direct investment and protection of the intellectual property rights. Moving into the next stage of regional integration, the creation of the European Monetary Union and the introduction of the Euro is based on sound foundations of the Common market. The Union believed that creating a Single market with a single currency will help to defend its economic interests more effectively. However, there were some weaknesses in the creation and functioning of the European Monetary Union, which were highlighted at the beginning of the global financial crisis in mid 2008 and the beginning of 2009. The Euro depreciated on several occasions and its value against other world currencies faced significant deduction. Total foreign trade of the Union also faced the biggest decline since the very beginning of the existence of the Union - 18% in 2009 compared to 2008. Unpredictable movements of the Euro undoubtedly will have a direct effect on the volume of trading and the Union's foreign trade positions. Therefore, the question of urgent importance is how to preserve the stability of the Euro, and thus macroeconomic stability and sustainability of the European Union.
Influence of the Euro on the foreign trade exchange of the European Union
Докторска дисертација одбранета во 2013 година на Економскиот факултет во Скопје, под менторство на проф. д–р Ирена Кикеркова.